Orders for Curfew: Extraordinary Measures with Ordinary Law in Struggle against Epidemic Disease - Ulusoy, Demet Celik; Uzuner, Emine (Istanbul Univ, Fac Law, 2021)
A new type of coronavirus epidemic affects the entire world. It requires governments to make quick and impactful decisions that push the limits of the constitutional state. There is no doubt that this period is extraordinary due to the circumstances of the situation and the consequences it produced. However, political power is limited in a democratic state based on the rule of law, whether circumstances are ordinary or extraordinary. Legal boundaries get pushed in exceptional circumstances within the framework of existing rules. Ordinary law must offer appropriate tools to combat extraordinary times. In the absence of these tools, extraordinary law is usually enforced. In the process, the Turkish Republic of Northern Cyprus (TRNC) Government has started to implement rapid measures to prevent epidemics. This study focuses on the legal dimension of the curfew. It reveals the outcome of the cessation of fundamental rights and freedoms without the need for an emergency declaration. The curfew will be evaluated based on the constitutional principles and the constitutionality of epidemic measures taken under the usual law regulations.
Keywords: TRNC Constitution; Curfew; Freedom of Movement and Residence; Orders; Fundamental Freedom and Rights in TRNC